2022
DOI: 10.1155/2022/5397449
|View full text |Cite
|
Sign up to set email alerts
|

Opium Use and Cancer Risk: A Comprehensive Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background. Epidemiological studies have reported inconsistent associations between opium use and cancer risk. We therefore conducted a systematic review and meta-analysis to investigate the relationship between opium use and cancer risk. Methods. We searched PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until February 2021 and references of retrieved relevant articles for observational studies that reported the risk of cancer in relation to opium use. Random-effects models were used to calculate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(201 reference statements)
0
10
0
Order By: Relevance
“…We also conducted an appraisal of the most important aspects of study quality, and documented a lack of cumulative exposure information, which might be further explored in future studies of opium consumption and cancer risk. Although other meta-analyses have been recently published on opium consumption and cancer risk [10][11][12][13][14], our systematic review is the most up to date, and has carefully considered a range of methodological sources of bias in findings, according to domains of study quality assessment defined by the IARC Monographs volume 126 Working Group.…”
Section: Random Effects Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We also conducted an appraisal of the most important aspects of study quality, and documented a lack of cumulative exposure information, which might be further explored in future studies of opium consumption and cancer risk. Although other meta-analyses have been recently published on opium consumption and cancer risk [10][11][12][13][14], our systematic review is the most up to date, and has carefully considered a range of methodological sources of bias in findings, according to domains of study quality assessment defined by the IARC Monographs volume 126 Working Group.…”
Section: Random Effects Modelmentioning
confidence: 99%
“…Here, we aimed to supplement the recent qualitative IARC cancer hazard evaluation by conducting an extended systematic review and a quantitative meta-analytic assessment of the role of opium consumption and risk for selected cancers, including cancers of the urinary bladder, larynx, lung, oesophagus, stomach, and pancreas [9]. This analysis therefore represents the most comprehensive systematic review and meta-analysis to date [10][11][12][13][14]. We specifically considered in detail exposure assessment quality, and the impact of various potential methodological sources of bias and confounding on meta-analytic findings according to a registered protocol.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ]. The analysis found that individuals who had ever used opium had a 3.53 times greater risk of developing any type of cancer, compared to those who had never used opium [ 13 ]. On the other hand, by meta-analysis investigation, the relationship between opium consumption and bladder cancer was found by studying 11 case–control, five cross-sectional and one cohort case.…”
Section: The Potential Link Between Opium and Cancermentioning
confidence: 99%
“…In an epidemiological case-control study, Shakeri et al [99] found that an emerging esophageal cancer cell carcinoma risk factor can be opium. To evaluate the association between opium use and cancer risk, the meta-analysis review of 21 observational studies, with a combined sample size of 64 412 individuals and 6658 cases of cancer was carried out by Mansouri et al [13]. The analysis found that individuals who had ever used opium had a 3.53 times greater risk of developing any type of cancer, compared to those who had never used opium [13].…”
Section: The Potential Link Between Opium and Cancermentioning
confidence: 99%
See 1 more Smart Citation